2004
DOI: 10.1056/nejmoa031049
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the Metabolic Syndrome in Children and Adolescents

Abstract: The prevalence of the metabolic syndrome is high among obese children and adolescents, and it increases with worsening obesity. Biomarkers of an increased risk of adverse cardiovascular outcomes are already present in these youngsters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

144
2,028
20
185

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,886 publications
(2,377 citation statements)
references
References 29 publications
144
2,028
20
185
Order By: Relevance
“…Widespread and extreme obesity are more common now (1) , combined with an obesogenic environment (9) ; so current estimates may underestimate the strength of tracking of obesity between childhood and adulthood in contemporary populations. Additionally, research has demonstrated that many obese children already manifest some metabolic complications, including impaired glucose tolerance, dyslipidaemia, hypertension, fatty liver disease and systemic low-grade inflammation (59)(60)(61) .…”
Section: Methodological Considerations: Sampling and Assessmentmentioning
confidence: 99%
“…Widespread and extreme obesity are more common now (1) , combined with an obesogenic environment (9) ; so current estimates may underestimate the strength of tracking of obesity between childhood and adulthood in contemporary populations. Additionally, research has demonstrated that many obese children already manifest some metabolic complications, including impaired glucose tolerance, dyslipidaemia, hypertension, fatty liver disease and systemic low-grade inflammation (59)(60)(61) .…”
Section: Methodological Considerations: Sampling and Assessmentmentioning
confidence: 99%
“…Search protocol Systematic database searches for abstracts and full-length manuscripts were performed on Ovid MEDLINE s (MEDL) 10,2004. Firstly, four categorical searches were conducted using the following 'keywords': (1) 'weight training,' 'strength training,' 'exercise,' 'exercise therapy,' 'weightlifting,' 'physical fitness,' or 'physical activity' (yielded 293 106 studies), (2) 'child', 'adolescent', or 'pediatrics' (yielded 1 795 359 studies), (3) 'body fat,' 'body weight,' or 'body composition' (yielded 325 759 studies) and (4) 'overweight,' 'obese' or 'obesity' (yielded 53 875 studies).…”
Section: Methodsmentioning
confidence: 99%
“…98 As in adults, excessive visceral fat (central obesity) is associated with an increased disease risk in children and adolescents, particularly for components of the 'metabolic syndrome.' [9][10][11][12][13][14] The waist circumference measure, a proxy of visceral fat, is uniformly included in the diagnosis of the 'metabolic syndrome' in both children and adults. 99 Safe and effective treatments for central obesity in youth are urgently needed, given the increasing prevalence of overweight in youth, [1][2][3][4][5] and that the prevalence of 'metabolic syndrome' in overweight children and adolescents has been reported to be as high as 29-50%, 10,13 and rising.…”
Section: Central Obesitymentioning
confidence: 99%
See 2 more Smart Citations